Księgowi a certyfikacja - Koczar, Joanna (Accountants - Certificate, 2007)
The evolution of accountant's profession is related to the development of accountancy. The range of accountants activities and their responsibility are a reason to pose a question on the introduction of this profession standard. In Poland this problem is very important and it needs fast solution because Polish law applies different requirements to accountants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 229-232